2014
DOI: 10.1096/fj.13-249318
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐1 regulates chondrocyte phenotype by repressing histone deacetylase 4 during growth plate development

Abstract: MicroRNAs (miRs) are noncoding RNAs (17-25 nt) that control translation and/or mRNA degradation. Using Northern blot analysis, we identified that miR-1 is specifically expressed in growth plate cartilage in addition to muscle tissue, but not in brain, intestine, liver, or lung. We obtained the first evidence that miR-1 is highly expressed in the hypertrophic zone of the growth plate, with an 8-fold increase compared with the proliferation zone; this location coincides with the Ihh and Col X expression regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Thus, caspase seems to be the only connection between elevated p38 activity and increased HDAC4 degradation in chondrocytes. In addition to the experimental evidence supporting the HDAC4/Runx2 interaction provided in this manuscript and by Vega et al, 2004, we also showed HDAC4 inhibits Runx2 promoter in a dose-dependent manner (Li et al, 2014). Arnold et al also showed that HDAC4 regulates the chondrocyte hypertrophy through MEF2 (Arnold et al, 2007).…”
Section: Resultssupporting
confidence: 63%
“…Thus, caspase seems to be the only connection between elevated p38 activity and increased HDAC4 degradation in chondrocytes. In addition to the experimental evidence supporting the HDAC4/Runx2 interaction provided in this manuscript and by Vega et al, 2004, we also showed HDAC4 inhibits Runx2 promoter in a dose-dependent manner (Li et al, 2014). Arnold et al also showed that HDAC4 regulates the chondrocyte hypertrophy through MEF2 (Arnold et al, 2007).…”
Section: Resultssupporting
confidence: 63%
“…Runx2 is a well known transcriptional factor that strongly induces Col X, Ihh and MMP-13 production[37-40]. Our previous studies[21] showed that CaMKIV modulates chondrocyte differentiation through regulating Runx2 promoter activities via HDAC4 subcellular localization during growth plate development.…”
Section: Discussionmentioning
confidence: 99%
“…MiR1 is highly expressed in the hypertrophic zone of growth plate cartilage, some 8fold higher than in the proliferation zone [77] . MiR1 strongly promotes chondrocyte proliferation and differentiation, including induction of the expression of chondrocyte markers Indian hedgehog and Col X, and acts by targetting HDAC4.…”
Section: Chondrocyte Differentiationmentioning
confidence: 99%